The Hungarian Retail Sales Tax in the Changing EU Context - Lovas, Dóra (Review of European and Comparative Law, 2024)
In the last twenty years, Hungary has had three periods of special taxes (introduced as a result of the crises), but before and after 2010, and after the recession following the COVID-19 epidemic and the Russian-Ukrainian war, there were different legal policy reasons behind special taxes (including the retail sales tax). This raises questions as to whether the regulatory solutions implemented to address market failures during the first period are playing the same role today as they did in the past, and how their role has changed over the years. The introduced taxes often remain part of the general tax system, i.e. they are applied on a permanent basis (rather than on a temporary basis, as is usual with special taxes), and in 2023 they already accounted for almost 14% of total tax revenue (a higher proportion than, for example, corporate tax), which puts their role in the tax system in a different light. The Court of Justice of the European Union (CJEU) has repeatedly examined the EU framework, but it appears that the control has been weakened, mainly due to the impact of the current crises. At the same time, the Hungarian Constitutional Court is bound by the limits of the debt brake when examining the constitutional framework. The study explores the regulation of the Hungarian retail sales tax and its EU context, in particular with regard to the changes triggered by the crises. The introduced taxes often remain part of the general tax system, i.e. they are not applied on a temporary basis, and in 2023 they already accounted for almost 14% of total tax revenue (a higher rate than, for example, corporate tax), which puts their place in the tax system in a different light. The Court of Justice of the European Union (CJEU) has repeatedly examined the EU framework, but it appears that the control has been weakened, mainly due to the impact of the current crises, while the Hungarian Constitutional Court is bound by the limits of the debt brake when examining the constitutional framework.The study deals with the regulation of the Hungarian retail sales tax and its EU context, in particular with regard to the changes induced by the crises.